(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This scientific article examines (studies) the genealogical structure and territorial location (distribution) of the Boru tribe on the basis of pre-revolutionary, Soviet and modern written works, written sources, manuscripts and field materials of the author. Ethnotoponyms derived from the ethnonyms of the Boru tribe are written.